IMPLEMENTASI KEGIATAN PEMBIASAAN DALAM MENINGKATKAN KARAKTER TOLERANSI ANTAR UMAT BERAGAMA PADA ANAK USIA DINI (PENELITIAN KUALITATIF DESKRIPTIF UNTUK ANAK USIA 4-5 TAHUN DI TK LABSCHOOL JAKARTA) - Khalda Hamidah; Dina Kusuma Wardhani; Fadlullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Interfaith tolerance is one of the important character values that needs to be instilled in early childhood, particularly within a multireligious educational environment. This study aims to describe the implementation of habituation activities in enhancing the character of interfaith tolerance, to identify the challenges encountered, and to determine the solutions used in addressing those challenges among children aged 4-5 years at TK Labschool Jakarta. This study employed a qualitative descriptive approach. The research was conducted at TK Labschool Jakarta from April to May 2026, with the research subjects being the principal, classroom teachers, and children of group A2 totaling 25 children. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The validity of the data was tested through source triangulation and technique triangulation. The results show that: 1) the implementation of interfaith tolerance habituation was carried out through alternating prayers, proportional separation of religious classes, monthly worship programs, and interfaith social service activities; 2) the challenges encountered stemmed from the limited schedule of the Hindu religion teacher and the imitative phase in children who had not yet fully grasped the sacred essence of worship; 3) the solutions applied included empowering inclusion-support teachers, providing persuasive education, and strengthening communication with parents. This study concludes that consistent habituation activities, supported by synergy among the school, teachers, and parents, are effective in fostering the character of interfaith tolerance in early childhood. Keywords: habituation activities, character, interfaith tolerance, early childhood.